Kanamycin and Ofloxacin Activate the Intrinsic Resistance to Multiple Antibiotics in Mycobacterium smegmatis - Aleksey A. Vatlin; Olga B. Bekker; Kirill V. Shur; Rustem A. Ilyasov; Petr A. Shatrov; Dmitry A. Maslov; Valery N. Danilenko (Biology, 2023)
Drug resistance (DR) in Mycobacterium tuberculosis is the main problem in fighting tuberculosis (TB). This pathogenic bacterium has several types of DR implementation: acquired and intrinsic DR. Recent studies have shown that exposure to various antibiotics activates multiple genes, including genes responsible for intrinsic DR. To date, there is evidence of the acquisition of resistance at concentrations well below the standard MICs. In this study, we aimed to investigate the mechanism of intrinsic drug cross-resistance induction by subinhibitory concentrations of antibiotics. We showed that pretreatment of M. smegmatis with low doses of antibiotics (kanamycin and ofloxacin) induced drug resistance. This effect may be caused by a change in the expression of transcriptional regulators of the mycobacterial resistome, in particular the main transcriptional regulator whiB7.